Institutional Characteristics of Supporting Potato Farming in South Sulawesi. Issue 1 (October 2021) - Indrasti, R; Rawung, J B M; Sudolar, N R; Handoko, S; Nurjanani,
Abstract: Potatoes are one of the commodities that have been prioritized for development which considered as a source of carbohydrates, highly nutritious and have the potential for food diversification. In this case the institutional activities of potato farmers may contribute to support their agribusiness aspects. The purpose of the study was to analyze the feasibility of potato farming as well as to characterize the farmer institutions. Data collection was carried out through FGD (Focus Group Discussion) with 25 respondents of potato farmer group members and secondary data as supporting data. The survey was conducted in 2017 in South Sulawesi Province. Data were analyzed descriptively and R/C ratio was measured to determine the potato farming feasibility. The results showed that potato farming was feasible economically. The farmers were mostly active in supporting institutional activities, including group meeting activities, paying fees and extension activities.